Features of coronary heart disease in a cohort of tajik patients and the condition of the vascular endothelium in its different clinical forms - F. A. Shukurov; M. S. Tabarov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. In the Republic of Tajikistan, in recent years there has been a steady increase in cardiovascular diseases. In this regard, special attention is paid to coronary heart disease with its various manifestations, which can often cause permanent disability, even death. In recent decades, there has been great interest among research scientists in studying the functioning of the endothelium in various forms of coronary heart disease, as well as in individuals with post-infarction cardiosclerosis as a complication of coronary heart disease. Despite the large number of studies in this area, the role and relationship of some sensitive markers of endothelial dysfunction with the clinical course of various forms of coronary heart disease have not yet been determined. That is why its detailed study is of unconditional clinical interest and provides the opportunity for a deep understanding of its theoretical aspects. Purpose of the study: to study risk factors for cardiovascular diseases and markers of endothelial dysfunction in patients with stable angina pectoris in comparison with patients with post-infarction cardiosclerosis, i.e. previous myocardial infarction.Object and methods. Of 60 patients with various forms of coronary heart disease, whose average age was 62.6 ± 3.5 years, and 20 practically healthy individuals of the same age who made up the control group, three groups were formed: Group I (n = 20) included respondents without coronary heart disease; Group II (n = 30) included patients with stable angina pectoris of functional class II and III; Group III (n = 30) included patients who were diagnosed with post-infarction cardiosclerosis, i.e. previously suffered a myocardial infarction. Endothelial cell dysfunction was detected by determining desquamated endothelial cells, as well as by the activity of von Willebrand factor and the level of homocysteine in the blood plasma.Results. In the examined patients, risk factors for coronary heart disease in the form of arterial hypertension, physical inactivity and obesity were observed with greater frequency in persons with stable angina pectoris of functional class II, in contrast to those with functional class III. Patients with stable angina pectoris of functional class III all had chronic heart failure of varying severity (100%). Most patients had at least three risk factors for coronary heart disease. All persons with post-infarction cardiosclerosis had risk factors for coronary heart disease, while arterial hypertension was detected in 100%. Based on the indicators of endothelial dysfunction, it can be said that individuals in group III have a more severe functional and morphological condition (increased homocysteine levels, von Willebrand factor activity and the number of desquamated endothelial cells) compared to group II (p < 0.001).Conclusion. In all forms of coronary heart disease (stable exertional angina of functional class II, III and post-infarction cardiosclerosis), the content of desquamated endothelial cells in the blood serum, the activity of von Willebrand factor and homocysteine are increased. A positive correlation was established between the level of desquamated endothelial cells and the level of homocysteine, von Willebrand factor, fibrinogen and platelets. After complex therapy of patients with various forms of coronary heart disease, the functional state of the endothelium improves (decrease in the level of desquamated endothelial cells, homocysteine, von Willebrand factor).